Distribution amplitudes of heavy mesons and quarkonia on the light front - Serna, Fernando E. [UNESP]; Silveira, Roberto Correa da; Cobos-Martinez, J. J.; El-Bennich, Bruno [UNESP]; Rojas, Eduardo (Springer, 2020)
The ladder kernel of the Bethe-Salpeter equation is amended by introducing a different flavor dependence of the dressing functions in the heavy-quark sector. Compared with earlier work this allows for the simultaneous calculation of the mass spectrum and leptonic decay constants of light pseudoscalar mesons, the Du, Ds, Bu, Bs and Bc mesons and the heavy quarkonia eta c and eta b within the same framework at a physical pion mass. The corresponding Bethe-Salpeter amplitudes are projected onto the light front and we reconstruct the distribution amplitudes of the mesons in the full theory. A comparison with the first inverse moment of the heavy meson distribution amplitude in heavy quark effective theory is made.